Diabetes Mellitus dengan Penyulit Kronis - Poerwantoro, Bambang; Purnamasari, Endah (Majalah Kesehatan Pharmamedika, 2011)
The term diabetes mellitus describes a metabolic disorder of multiple aetiology characterized by chronic hyperglycaemia resulting from defects in insulin secretion, insulin action, or both. Diabetes mellitus cause a long–term damage, dysfunction and failure of various organs. The long–term effects of diabetes mellitus include macroangiopathy and microangiopathy complications, such as progressive retinopathy with potential blindness, nephropathy that may lead to renal failure, and increased risk of cardiovascular, peripheral vascular and cerebrovascular disease. This is a report of a case diabetes mellitus with macroangiopathy and microangiopathy complications.